A Data-Enabled Business Model for a Smart Healthcare Information Service Platform in the Era of Digital Transformation. (1st June 2021) - Su, Yu; Hou, Fei; Qi, Mingde; Li, Wanxuan; Ji, Ying
Abstract : Digital technology has promoted service innovation and provided effective technical support for public service innovation in recent years. Smart healthcare, a key element of smart city development, has gradually become an important issue in government administration. Digital technology is deeply embedded in healthcare services and reshapes value creation through digital transformation. This study combines data-enabled platform business models and value cocreation and adopts a case study approach to develop a business model for a medical information service platform that allows stakeholders to cocreate value through service exchange and resource integration in smart healthcare ecosystems, promotes efficient and coordinated applications of information, and realizes innovative development in the medical industry.